2015
DOI: 10.1016/j.aop.2015.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Role of information theoretic uncertainty relations in quantum theory

Abstract: Uncertainty relations based on information theory for both discrete and continuous distribution functions are briefly reviewed. We extend these results to account for (differential) Rényi entropy and its related entropy power. This allows us to find a new class of information-theoretic uncertainty relations (ITURs). The potency of such uncertainty relations in quantum mechanics is illustrated with a simple two-energy-level model where they outperform both the usual RobertsonSchrödinger uncertainty relation and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 84 publications
0
71
0
Order By: Relevance
“…The dominant contribution here is given by I 3 . Substituting asymptotics (44) in I 3 , making the change of variable t := x 4n and using ( [67], Lemma 2.1) we arrive to…”
Section: Proof Of Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant contribution here is given by I 3 . Substituting asymptotics (44) in I 3 , making the change of variable t := x 4n and using ( [67], Lemma 2.1) we arrive to…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…For a revision of their properties see [38,39,40,41,42,43,44] and the reviews [45,46]. The Rényi entropies and their associated uncertainty relations have been widely used to investigate a great deal of quantum-mechanical properties and phenomena of physical systems and processes [29,45,46,44], ranging from the quantum-classical correspondence [47] and quantum entanglement [48] to pattern formation and Brown processes [49,50], fractality and chaotic systems [51,52], quantum phase transition [53] and disordered systems [54]. Moreover, the knowledge of these quantities allows us to reconstruct the corresponding probability density under certain conditions [41,55].…”
Section: Introductionmentioning
confidence: 99%
“…This type of expression was studied in [18,19] where it was shown that the only class of solution of (5) is…”
mentioning
confidence: 99%
“…According to Density Function theory, a many fermion system can be completely characterized by the single particle distribution density, which is is that an increase of S(mom) corresponds to a decrease of S(pos) and vice-versa, which indicates that a diffuse density distribution ρ(p) in momentum space is associated with a localized density distribution ρ(r) in configuration space [3][4][5][6][7][8][9][10][11][12]. In this paper, we investigate the use of the position space information entropy as an indicator of the entanglement for nanostructure system.…”
Section: Ijetst-vol||04||issue||08||pages 5388-5394||august||issn 23mentioning
confidence: 99%